Isoliquiritigenin inhibits melanogenesis, melanocyte dendricity and melanosome transport by regulating ERK‐mediated MITF degradation. Issue 2 (15th December 2019) - Lv, Jinpeng; Fu, Ying; Cao, Yan; Jiang, Songzhou; Yang, Ying; Song, Guoqiang; Yun, Changjun; Gao, Rongyin
Abstract: Isoliquiritigenin (ISL), a flavonoid component from the hydrolysis products of licorice root. It has been reported that ISL inhibited melanogenesis by suppressing the tyrosinase activity in human melanocytes. Recently, ISL was found to induce melanin degradation in human epidermal keratinocytes. However, the role of ISL in pigmentation is not fully understood. In the current study, we aimed to investigate the effects of ISL on pigmentation, and further explored the underlying mechanism. Our results suggested that ISL suppressed basal and α‐MSH‐, ACTH‐ and UV‐induced melanin synthesis, in addition to inhibiting melanocyte dendricity and melanosome transport. ISL played these roles mainly by activating the extracellular signal‐regulated protein kinase pathway. Once activated, it induced microphthalmia‐associated transcription factor degradation and decreased the expression of tyrosinase, TRP‐1, DCT, Rab27a and Cdc42, finally inhibited melanogenesis, melanocyte dendricity and melanosome transport. Our findings suggested that ISL exhibited no cytotoxicity in our research, it may prove quite useful as a safer natural skin‐whitening agent.